Mimosapudica L. aqueous extract protects mice against pilocarpine–picrotoxin kindling-induced temporal lobe epilepsy, oxidative stress, and alteration in GABAergic/cholinergic pathways and BDNF expression - Mambou, Hart Mann Alain Youbi; Pale, Simon; Bopda, Orelien Sylvain Mtopi; Jugha, Vanessa Tita; Musa, Nji Seraphin Ombel; Ojongnkpot, Tambong Ako; Wanyu, Bertrand Yuwong; Bila, Raymond Bess; Herqash, Rashed N.; Shahat, Abdelaaty A.; Taiwe, Germain Sotoing (Frontiers in Pharmacology, 2025)
Ethnopharmacological studies revealed that the leaves and stems of Mimosa pudica L. (Fabaceae) are widely used for the treatment of epilepsy. This study sought to investigate the effects of the aqueous extract of Mimosa pudica leaves and stems against pilocarpine–picrotoxin kindling-induced temporal lobe epilepsy in mice and its implication on oxidative/nitrosative stress, GABAergic/cholinergic signalling, and brain-derived neurotrophic factor (BDNF) expression. The animals were treated for seven consecutive days as follows: one normal group and one negative control group that received orally distilled water; four test groups that received orally four doses of Mimosa pudica (20, 40, 80, and 160 mg/kg), respectively; and one positive control group that received 300 mg/kg sodium valproate intraperitoneally. One hour after the first treatment (first day), status epilepticus was induced by intraperitoneal injection of a single dose of pilocarpine (360 mg/kg). Then, 23 hours after the injection of pilocarpine to the mice, once again, they received their different treatments. Sixty minutes later, they were injected with a sub-convulsive dose of picrotoxin (1 mg/kg), and the anticonvulsant property of the extract was determined. On day 7, open-field, rotarod, and catalepsy tests were performed. Finally, the mice were sacrificed, and the hippocampi were isolated to quantify some biochemical markers of oxidative/nitrosative stress, GABAergic/cholinergic signalling, and BDNF levels in the hippocampus. Mimosa pudica extracts (160 mg/kg) significantly increased the latency time to status epilepticus by 70.91%. It significantly decreased the number of clonic and tonic seizures to 9.33 ± 1.03 and 5.00 ± 0.89, and their duration to 11.50 ± 2.07 and 6.83 ± 0.75 s, respectively. Exploratory behaviour, motor coordination, and catalepsy were significantly ameliorated, respectively, in the open-field, rotarod, and catalepsy tests. Pilocarpine–picrotoxin-induced alteration of oxidant–antioxidant balance, GABA-transaminase stability, acetylcholinesterase/butyrylcholinesterase activity, and neurogenesis were attenuated by the extract (80–160 mg/kg). This study showed that the aqueous extract of Mimosa pudica leaves and stems ameliorated epileptogenesis of temporal lobe epilepsy and could be used for the treatment of temporal lobe epilepsy.